Alleged Delay in Notification of Takeover of Shares of Pt Kadi Indonesia Manufaktur by Nippo Corporation Decision: 16/KPPU-M/2023 - Bunyamin, Bubun; Rosidah, Rosidah; Wijaya, Dion Untung; Yuliarpan, Pipit (PT FORMOSA CENDEKIA GLOBAL, 2024)
The case of late notification of the takeover of PT Kadi Indonesia Manufaktur (PT KIM) shares by Nippo Corporation has become an important highlight for law enforcement in the Indonesian capital market. This violation has the potential to have a negative impact on the capital market, especially for PT KIM investors, and could damage investor confidence in the existing system. This research analyzes two important aspects: the effectiveness of the Rp. 1 billion fine sanction imposed by the KPPU on Nippo Corporation, and the adequacy of the current share takeover notification mechanism. The results of the analysis show that the effectiveness of fines and notification mechanisms still needs to be strengthened to ensure compliance with Law no. 5 of 1999. Furthermore, this research provides conclusions and suggestions for improving the effectiveness of law enforcement and preventing similar violations in the future. These suggestions include strengthening regulations and law enforcement, increasing transparency and education, increasing cooperation between agencies, utilizing technology, and strengthening the role of the community. Further research is recommended to explore various aspects related to this case, such as economic impacts, comparisons with other countries, roles and responsibilities of related parties, factors driving violations, and the effectiveness of education and outreach